2004
DOI: 10.1021/ma0349130
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Chain Branching in Polyethylene in the Solid State and Melt via 13C NMR Spectroscopy and Melt NMR Relaxation Time Measurements

Abstract: Branch contents in sparsely short-chain branched polyethylenes ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 33 publications
5
95
0
Order By: Relevance
“…This observation is in agreement with Fujita et al (See ref 2.) Chain branching in these polymers is investigated following the solid-state NMR method of Pollard et al 23 The studies performed in the melt state of the disentangled polyethylenes show the nonexistence of branches even up to the 10 000 C atoms, with the upper limit of the method applied. Therefore, it could be stated that the method used for polymerization in this publication yields linear polyethylenes that are free of branches.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in agreement with Fujita et al (See ref 2.) Chain branching in these polymers is investigated following the solid-state NMR method of Pollard et al 23 The studies performed in the melt state of the disentangled polyethylenes show the nonexistence of branches even up to the 10 000 C atoms, with the upper limit of the method applied. Therefore, it could be stated that the method used for polymerization in this publication yields linear polyethylenes that are free of branches.…”
Section: Resultsmentioning
confidence: 99%
“…[30] A good resolution of the carbon signal at branching points, as well as a large signal to noise ratio, are required in 13 C NMR quantitative analyses. [15,[31][32][33] Achieving such a high-quality 13 C NMR spectrum, however, is very difficult due to the low natural abundance of the 13 C isotope. Specifically, this low abundancy results that the signal intensity of branched carbons is a factor of 100-1000 lower than that of the backbone carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
“…An early study was reported by Hatfield et al using a 200 MHz spectrometer ( 1 H resonance), [34,35] followed by intensive works of Wilhelm, Kaminsky and their co-workers. [33,36,37] Compared (5 of 20) 1600012 to the solution NMR, which has a sample concentration less than 20 wt%, the melt and solid-state 13 C NMR generate a higher sample filling factor, resulting in a higher sensitivity towards the presence of sparsely branched side chains and end groups in POs. This technique currently allows the characterization of branch lengths up to 16 carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
“…The simple spectral features also suggest that the sample is very unlikely to show large inhomogeneity. Based on the characteristic values and studies of polymers containing similar functional segments [47,48], all peaks are assigned. The peaks at 29.6 and 36.1 ppm were respectively attributed to the methine and methylene groups present in the main chain.…”
Section: Cp/mas Nmr Spectroscopymentioning
confidence: 99%